Effective Management Strategies for Small Businesses - Mahi Raj (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
In this paper, we investigate what makes for good administration of small businesses. While small businesses play an important role, they frequently encounter difficulties in areas such as talent acquisition and retention, cash flow management, technology adoption, meeting regulatory requirements, and achieving a sustainable level of growth. This study analyzes these essential management techniques and offers advice based on the latest findings and industry standards. In light of these findings, it seems reasonable to assume that small businesses which place a premium on and successfully implement these management strategies will have a greater chance of long-term success and growth. Success and positive social and community effect are more likely for small companies that take a proactive management approach and keep up with industry trends and best practices.